Nutritional problems among patients affected by cancer during chemotherapy - Kamińska, Marzena; Kolak, Agnieszka; Tymicka, Renata; Bronikowska, Agnieszka (Medical Studies/Studia Medyczne, 2015)
Chemotherapy is one of the primary methods of treating cancer. Symptoms occurring during this form of therapy affect patients’ general health status, cause malnutrition, and deteriorate the quality of life of oncology patients, which results in cachexia. Malnutrition during treatment and the resulting bad general health status of patients may lead to disqualification from chemotherapy treatment. Cachexia is a complex and multi-factorial process, characterised by the nearly unknown mechanism of its development. What is extremely crucial is the evaluation of the state of malnutrition among patients qualified for cytostatic therapy and regular control of this state during therapy and immediately after its termination. Clinical practice indicates the importance of applying pharmacotherapy, nutritional treatment, and targeted education for the patient and their closest family regarding diet and correct behaviour, which significantly reduces anxiety and stress.